Pelayanan Swamedikasi Asam Mefenamat di Beberapa Apotek Kabupaten Lamongan (Studi dengan Metode Simulasi Pasien) - Lestari, Mila Ayu Puji; Amarullah, Adinugraha; Wahyuni, Khurin In (Universitas PGRI Adi Buana, Surabaya, 2021)
Pharmacy service is one of the health services in Indonesia which is required to change its orientation from drug oriented to patient oriented. Pharmacy service activities that initially focused on managing drugs as commodities must be transformed into comprehensive services aimed at improving the quality of life of patients. Self-medication or self-medication is an individual's effort to choose and use medicines to treat self-recognized diseases or symptoms. This study aims to determine mefenamic acid self-medication services in several pharmacies in Lamongan district. This research was conducted using purposive sampling technique. From these techniques 49 pharmacies were selected as samples. The data collection method used patient simulation. The instruments used in this study were check lists, research scenarios and research protocols. This research has passed ethics with approval number 093/HRECC.FODM/III/2021. Of the 49 pharmacies, patient assessments were asked when performing self-medication services, namely for whom the drug was given 2 (4.08 percent), patient 1 address (2.04 percent), patient age 2 (4.08 percent), anything symptoms that arise 4 (8.16 percent), how long 3 (6.12 percent). For the determination of recommendations from 49 pharmacies that provide self-medication services, the most information is given, namely the number of drugs received 33 (67.35 percent), replacement of generic or patent drug brands 16 (32.65 percent), drug prices 49 (100 percent). For drug information, the most widely given drug therapy objectives were 4 (8.16 percent), rules of use 4 (8.16 percent), side effects 2 (4.08 percent), symptoms of side effects 1 (2.04 percent) , overcoming side effects 1 (2.04 percent), and giving advice 1 (2.04 percent). From this research, the role of pharmacists and other pharmacists in providing mefenamic acid self-medication services is still lacking and needs to be improved.